CARIES PREVALENCE AMONG 5-7 - YEAR-OLD CHILDREN IN NORTHEAST BULGARIA - Evgeni Dimitrov; Milena Georgieva; Radosveta Andreeva; Мariana Dimova-Gabrovska; Hristina Arnautska (Peytchinski Publishing, 2017)
The aim of the current epidemiological research is to present the caries prevalence in children and on tooth surfaces in 5-7 - year-olds from Varna. The object of the current epidemiological research is a representative part of 100 5-7 - year-old children, randomly chosen. The unit of observation is temporary and early mixed dentition, primary molars and their occlusal and approximal surfaces. The survey was carried out acc ording to WHO's criteria. For caries risk assessment it is used the ICDAS system, where for a diagnostic limit was chosen d3mft. As a result from the conducted epidemiological research it is concluded that in this age group 93% of the children have experience with caries and barely 7% are caries free (dmft/ DMF(T+t)=0). The intensity d1-3mft and D1-3MF(T+t) of the caries have an average value of 5,76 ± 2,9. The relative share of the approximal caries of the primary molars on maxilla and mandible is 81,5% for both. The relative share of the occlusal caries is 19,6%. In the current research, it is not established statistically significant difference (P>0,05) concerning approximal lesions on first and second primary molar. There is the statistically significant difference (P<0,05) in the relative share of occlusal caries, which mainly affects the occlusal surface on the second primary molar. The relative share of the children without occlusal caries on primary molar is 60%, while those without approximal caries is barely 18%.